Growth Through Education: The Narratives of Older Adults - Bjursell, Cecilia (Frontiers in Sociology, 2019)
The focus of Narrative Gerontology is placed on stories about the ageing process. In the present paper, the learning of older adults in a Senior University context is captured by means of stories written by the participants themselves. The examination of older adults’ stories, as they look back on life or any narrative that connected to a specific area of life, can contribute to our understanding of growth later in life. The aim of the study is to examine how growth manifests itself later in life. Participants at Senior University were asked to share their experiences of education later in life. Participation was voluntary and the identity of each participant was kept anonymous for the purpose of the research project. 53 stories written by Senior University participants (n = 38 women and 15 men) were analyzed according to: (i) an inductive analysis of the stories that resulted in a description of the main topics addressed in the stories, and (ii) a deductive analysis that invoked a theoretical framework concerning the existential aspects of older adults’ learning, including ‘corporeality’, ‘relationality’, ‘spatiality’, ‘temporality’, and ‘materiality’. The two analyses were compared, and it was noted that ‘relationality’ and ‘spatiality’ corresponded to the educational experiences in the stories. ‘Relationality’ was observed to be concerned with the social dimensions of life; but in the context of Senior University, ‘relationality’ was strongly intertwined with the learning process. ‘Spatiality’ addressed how older adults relate to physical- and mental space. Participation at Senior University entailed an expansion of both physical- and mental space for the participants. A number of tensions were identified in the stories. One the one hand, the stories can be interpreted as illustrations of moving forward and embracing continued growth and development. On the other hand, the stories can be interpreted as illustrations of resistance towards ageing and decline. Since life is complex and contradictory, multiple, and even contradictory plots, co-exist in life stories.